Hyperkalemia in chronic peritoneal dialysis patients - Andrew B. Elliott; Karim M. M. Soliman; Michael E. Ullian (Renal Failure, 2022)
Background. Chronic peritoneal dialysis (PD) patients often develop hypokalemia but less commonly hyperkalemia. Methods. We explored incidence and mechanisms of hyperkalemia in 779 serum samples from 33 patients on PD for 1 − 59 months. Normal serum potassium concentration was defined as 3.5 − 5.1 meq/l. Results. Mean monthly serum potassium concentrations were normal (except for 1 month), but we observed hypokalemia (<3.5 meq/l) in 5% and hyperkalemia (>5.1 meq/l) in 14% of 779 serum samples. Incidence of hyperkalemia did not change over time on PD: Year 1 (15%), Year 2 (11%), Year 3 (19%), Years 4–5 (22%). Hyperkalemia was mostly modest but occasionally extreme [5.2–5.4 meq/l (55%), 5.5–5.7 meq/l (21%), 5.8–6.0 meq/l (10%), >6.0 meq/l (14%)]. Of 31 patients (2 excluded due to brief PD time), 39% displayed hyperkalemia only, 23% displayed hypokalemia only, and the remainder (38%) displayed both or neither. Comparing hypokalemia-only with hyperkalemia-only patients, we found no difference in potassium chloride therapy, medications interrupting the renin-angiotensin system, small-molecule transport status, and renal urea clearance. We compared biochemical parameters from the hypokalemic and hyperkalemic serum samples and observed lower bicarbonate concentrations, higher creatinine concentrations, and higher urea nitrogen concentrations in the hyperkalemic samples (p < 0.001 for each), without difference in glucose concentrations. Conclusion. We observed hyperkalemia 3 times as frequently as hypokalemia in our PD population. High-potassium diet, PD noncompliance, increased muscle mass, potassium shifts, and/or the daytime period without PD might contribute to hyperkalemia.